The Challenges in Implementation of Halal Vaccine Certification in Malaysia - Johari Ab Latiff; Zalina Zakaria; Sa'adan Man (Journal of Food and Pharmaceutical Sciences, 2021)
The global halal pharmaceutical sector is valued at USD 132 billion by 2021. (Pharmaceuticals, 2020). This sector is seen as a high priority development area. Apart from food products, Muslim consumers are also becoming more aware of halal pharmaceuticals. They are beginning to see the potential detrimental effects created by product development, testing, and production, all of which could be deviating from the halal values. Based on this uncertainty, the public at large is increasingly questioning the sources of their pharmaceutical products. Under such circumstances, the situation of children contracting contagious diseases has been noted to be on the rise in Malaysia, especially in the last few years. As a result, health authorities are concerned that there would be parents who may reject the immunization programs for their children out of the fear that the vaccines used may infringe on some strict religious rules. (Johari Ab Latiff, 2018) A conservative Muslim may sometimes reject the inoculation over concerns that some vaccines were derived from contents of pigs or porcine, of which Muslims are forbidden to consume. Vaccines are part of the pharmaceutical products, and like all other pharmaceutical products, they can be developed using halal ingredients, which can replace the use of non halal contents or animal products and their derivatives for medication. The implementation of halal certification for vaccines is strictly bounded by Shariah law and Fatwa. Malaysia. As a Muslim country, Malaysia is widely and globally regarded as one of the pioneers in halal pharmaceuticals. This can be traced to its world first halal pharmaceutical standard which was introduced as MS 2424: Halal Pharmaceuticals – General Guidelines since 2012, with first revision in 2019. Nonetheless, from then until presently, Malaysia has not been able to provide halal certification for the vaccine products. The implementation of the halal certification for vaccine products in Malaysia may have been triggered by the use of non-halal or forbidden ingredients in the manufacturing of those vaccine products. Thus far, the Malaysian Standard of the MS 2424 is the only standard, and it is also only a general guide. There is a need to develop a more thorough manual that can be adhered to by pharmaceuticals. This necessity to certify vaccine products as halal for the context of Malaysia has thus put the Halal Certification Body, like JAKIM, to be in limbo